Existence of Solution to a Quadratic Functional Integro-Differential Fractional Equation - Karande, B. D.; Kondekar, S. N. (Communications in Mathematics and Applications, 2020)
An algebraic fixed point theorem involving the two operators in a Banach algebra is used to prove the existence of solutions to fractional order quadratic functional integro-differential equation in (\mathcal{R}_+\). Also, we establish the locally attractivity results and extremal solutions along with suitable example.